3D printing in spine surgery - Sheha, Evan D.; Gandhi, Sapan D.; Colman, Matthew W. (Annals of Translational Medicine; Vol 7, Supplement 5 (September 10, 2019): Annals of Translational Medicine (Focus on: “Current Trends and Advancements in Spine Surgery”), 2019)
The applications of three-dimensional (3D) printing, or additive manufacturing, to the field of spine surgery continue to grow in number and scope especially in recent years as improved manufacturing techniques and use of sterilizable materials have allowed for creation of 3D printed implants. While 3D printing in spine surgery was initially limited to use as visual aids in preoperative planning for complex pathology, it has more recently been used to create intraoperative patient-specific screw guides and templates and is increasingly being used in surgical education and training. As patient-specific treatment and personalized medicine gains popularity in medicine, 3D printing provides a similar option for the surgical fields, particularly in the creation of customizable implants. 3D printing is a relatively new field as it pertains to spine surgery, and as such, it lacks long-term data on clinical outcomes and cost effectiveness; however, the apparent benefits and seemingly boundless applications of this growing technology make it an attractive option for the future of spine surgery.